2017
DOI: 10.1016/j.celrep.2017.08.015
|View full text |Cite
|
Sign up to set email alerts
|

PCAF/GCN5-Mediated Acetylation of RPA1 Promotes Nucleotide Excision Repair

Abstract: The RPA complex can integrate multiple stress signals into diverse responses by activating distinct DNA repair pathways. However, it remains unclear how RPA1 elects to activate a specific repair pathway during different types of DNA damage. Here, we report that PCAF/GCN5-mediated K163 acetylation of RPA1 is crucial for nucleotide excision repair (NER) but is dispensable for other DNA repair pathways. Mechanistically, we demonstrate that the acetylation of RPA1 is critical for the steady accumulation of XPA at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 48 publications
3
66
0
Order By: Relevance
“…We also showed that GCN5, a family member of PCAF, could not acetylate H1K85ac, which may be due to their diverse complex formation with different subunits (58,59). Interestingly, we found that PCAF is gradually recruited to chromatin during DNA damage repair, which is supported by a recent report that PCAF is recruited to UV-induced DNA damage sites (60). These data suggest that HDAC1 and PCAF are responsible for DNA damage-induced H1K85ac dynamics.…”
Section: Discussionsupporting
confidence: 87%
“…We also showed that GCN5, a family member of PCAF, could not acetylate H1K85ac, which may be due to their diverse complex formation with different subunits (58,59). Interestingly, we found that PCAF is gradually recruited to chromatin during DNA damage repair, which is supported by a recent report that PCAF is recruited to UV-induced DNA damage sites (60). These data suggest that HDAC1 and PCAF are responsible for DNA damage-induced H1K85ac dynamics.…”
Section: Discussionsupporting
confidence: 87%
“…Thus, human premature aging disorders are strongly associated with defects in DSBR, BER, and NER . Furthermore, repair of DNA damage is an energy demanding process and it is becoming increasingly evident that DNA damage and persistent DDR‐linked cellular stress leads to mitochondrial dysfunction and metabolic defects . The following paragraphs discuss the molecular mechanisms underlying this signaling and how it relates to cellular bioenergetics/energy homeostasis and the cellular abundance of ATP and NAD + .…”
Section: Dna Damage Response Pathwaysmentioning
confidence: 99%
“…Moreover, RPA1 interacts with both WRN and DNA2L, thereby stimulating WRN-mediated double-stranded DNA end unwinding and DNA2L-mediated ssDNA degradation (20). Corresponding to its multifaceted engagement in various aspects of DNA metabolism, RPA1 has been shown to be regulated by various PTMs such as acetylation, phosphorylation, ubiquitination, and SUMOylation (21)(22)(23)(24). However, whether and how Kcr regulates the function of RPA1 are unclear.…”
Section: Introductionmentioning
confidence: 99%